2019
DOI: 10.1029/2019tc005586
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Incoming Plate Relief on Overriding Plate Deformation and Earthquake Nucleation: Cocos Ridge Subduction (Costa Rica)

Abstract: We present a 2-D P wave velocity model and a coincident multichannel seismic reflection profile characterizing the structure of the southern Costa Rica margin and incoming Cocos Ridge. The seismic profiles image the ocean and overriding plates from the trench across the entire offshore margin, including the structures involved in the 2002 Osa earthquake. The overriding plate consists of three domains: Domain I displays thin-skinned deformation of an imbricate thrust system composed of fractured rocks. Domain I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 73 publications
(135 reference statements)
0
16
0
4
Order By: Relevance
“…related to glacial/interglacial periods) and the subduction of topographic highs (e.g. seamounts, ridges [46][47][48][49] ) also affect forearc deformation and make the surface evolution difficult to decipher as it interferes with the aforementioned periodic topographic signal obtained despite constant kinematic and boundary conditions (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…related to glacial/interglacial periods) and the subduction of topographic highs (e.g. seamounts, ridges [46][47][48][49] ) also affect forearc deformation and make the surface evolution difficult to decipher as it interferes with the aforementioned periodic topographic signal obtained despite constant kinematic and boundary conditions (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…Husen et al, 2002;DeShon et al, 2003;Chaves et al, 2017), modelado geodésico (Feng et al, 2012;Kobayashi et al, 2014;Protti et al, 2014) y otros fenómenos sísmicos (Outerbridge et al, 2010). En la transición entre los segmentos Central y Sureste existen solamente un estudio de una secuencia sísmica (Arroyo et al, 2014b) y dos trabajos de sísmica activa (Bangs et al, 2015;Martínez-Loriente et al, 2019). Sin embargo, el segmento Sureste es aún el menos estudiado, debido principalmente a la relativa escasez de cobertura con estaciones sísmicas en el pasado y a la alta dificultad de acceso a la cordillera de Talamanca.…”
Section: Discussionunclassified
“…They further suggest that the geological structures found offshore Costa Rica were deformed during seismic slip-to-the-trench events instead of aseismic creep. Post-stack time migration of multichannel seismic data, interpreted together with velocity models from wide-angle seismic profiling, bathymetry and earthquake data (Martínez-Loriente et al 2019) have revealed a clear image of subducted seamounts 18 and 40 km away from the trench, and well resolved tectonic structures in the overriding plate. Here, the M w 6.4 2002 Osa earthquake nucleated at the seamount's leading flank.…”
Section: Introductionmentioning
confidence: 99%